2013
DOI: 10.1053/j.gastro.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Dual Oxidases Control Release of Hydrogen Peroxide by the Gastric Epithelium to Prevent Helicobacter felis Infection and Inflammation in Mice

Abstract: Background & Aims Dual oxidases (DUOX) are conserved NADPH oxidases that produce H2O2 at the epithelial cell surface. The DUOX enzyme comprises the DUOX and DUOXA (DUOX maturation factor) subunits. Mammalian genomes encode 2 DUOX isoenzymes (DUOX1–DUOXA1 and DUOX2–DUOXA2). Expression of these genes is upregulated during bacterial infection and chronic inflammatory diseases of the luminal gastrointestinal tract. The roles of DUOX in cellular interactions with microbes have not been determined in higher vertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 48 publications
1
100
0
Order By: Relevance
“…We furthermore determined that TlpD mediates a repellent response to compounds that generate ROS. Oxygen and ROS are ubiquitous in the stomach, where H. pylori resides, arising from both epithelial and immune cells (31,50). Our findings thus suggest a model in which TlpD is used to help H. pylori avoid regions with high ROS, as discussed below.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We furthermore determined that TlpD mediates a repellent response to compounds that generate ROS. Oxygen and ROS are ubiquitous in the stomach, where H. pylori resides, arising from both epithelial and immune cells (31,50). Our findings thus suggest a model in which TlpD is used to help H. pylori avoid regions with high ROS, as discussed below.…”
Section: Discussionmentioning
confidence: 65%
“…H. pylori is exposed to ROS produced in the stomach by both epithelial and phagocytic cells (31,50,64). The ability to survive ROS appears to be critical during H. pylori colonization, as antioxidant enzymes are highly expressed by this microbe, and mutants lacking them are attenuated in colonizing animal hosts (43,65).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Drosophila, Caenorhabditis elegans, and zebrafish intestine have shown that epithelial production of H 2 O 2 is part of the host response to gut infection and is involved in microbial clearance and responses to gut symbionts and pathogens (28)(29)(30). In mammals, a similar role has been postulated based on studies of pathogen infection in stomach and airway ECs (31,32).…”
Section: Discussionmentioning
confidence: 75%
“…In non-vertebrates, such as Drosophila, zebrafish, and Caenorhabditis elegans, a growing cluster of data supports the indispensable role of Duox in gastrointestinal control of commensal, foodborne, or pathogenic microorganisms [61][62][63]. Recently, an interesting study on DuoxA double knockout mice confirmed the protective role of Duox2-derived H 2 O 2 , as it prevented the gastric colonization by Helicobacter felis and attendant inflammatory responses [64]. This study was the first in vivo genetic demonstration in a mammalian organism of how Duox can control the colonization of a noninvasive pathogen of the mucus layer.…”
Section: Duox1 and Duox2mentioning
confidence: 96%